Configuração do trabalho docente e a instrução primária em Sergipe no século XIX (1827-1880) - Amorim, Simone Silveira (2012)
This thesis has as its objective to analyse the get starting process of the Primary Instruction in the 19th century as for teaching laws and the press, having as perspective the professional teaching configuration movement, analysing the representations and experiences of the agents involved in this process in Sergipe. The analitical cathegories of Pierre Bourdieu (1960), Norbert Elias (1990, 2011), Roger Chartier (2002) helped understand how the teaching profession got organized and its representations related to the elementary school teaching and how the professional habitus settled down thought to the project of Brazil as a nation, inside a civilized process. This research was composed based on the theoretical basis of the Cultural History, therefore, the newspapers from Instituto Histórico e Geográfico de Sergipe and from Instituto Tobias Barreto were researched; the official mail exchanged by the teachers and the State and its agents, records of Diretoria da Instrução Pública and the teaching coordinators, the students frequency maps, the educational Laws at that time found at Arquivo Público de Sergipe were researched as well. In the first chapter, the institutionalization process of the school and of the teaching profession configuration was analyzed thru the Laws, as well as the importance of Normal School in the process of institutionalization of elementary teachers graduation. The second chapter has the objective to identify the strategies used by the intellectual and political elite to convince the sergipana literated population that the Public Instruction in Sergipe was under development and according to what was updated at that time, that´s why disputes in the teaching field were also studied thru newspapers. This analysis is done based on the speeches performed at Assembleia Provincial Sergipana and on the Public Instruction Reports published in the newspapers, as well as on newspapers ads about instruction and education. Having the goal to understand how the seek for being legitimated was accomplished by the teachers and also the representation they wanted to reach before the sergipana society, aspects related to exams and students exams published in newspapers were discussed. The school maps were also analyzed in order to know the elementary school students profile. Newspaper ads and commercials (teachers, private institutions, among others) were also objective of analyses in the third chapter.It is possible to conclude that the teaching profession was built among advances and withdrawers throughout the laws proposed by the State as it brought to itself the responsibility to change Brazil into a nation. It was possible to get that the elementary school teachers made some effort to legitimate the relationship with the population and with the local teaching authorities, in a strategic way, especially by the press and official mails.